Risk management at the top : a guide to risk and its governance in financial institutions - Laycock, Mark, 1959- (Chichester, West Sussex, United Kingdom : John Wiley and Sons, Inc., 2014)
With over 30 years' experience of risk management in banks, Mark Laycock provides a comprehensive but succinct non-technical overview of risk and its governance in financial institutions. Bridging the gap between texts on governance and the increasingly technical aspects of risk management the book covers the main risk types experienced by banks - credit, market, operational and liquidity - outlines those risks before considering them from a governance perspective including the Board and Executive Management. Addressing terminology issues that can confuse dialogue, and by providing a.
Risk Oversight. Introduction -- Risk Oversight -- Risk Oversight. Risk : An Overview -- Risk Oversight -- Risk Management -- Risk Appetite -- Risk Culture -- Specific Risks -- Specific Risks. Credit Risk -- Market Risk -- Operational Risk -- Liquidity Risk -- Other Risks -- Risk Interactions -- Regulatory Environment -- Regulatory Environment. Regulatory Environment -- Disclaimer Regarding Excerpts from S & P Materials.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Financial institutions -- Management; Banks and banking -- Risk management; Corporate governance; Risk management; Banks and banking -- Risk management; Corporate governance; Financial institutions -- Management; Risk management; BUSINESS & ECONOMICS -- Finance; Electronic books; Electronic books